Concomitant Sertoli and Leydig Cell Tumor of the Testis: A Case Report - Tazi, Mohammed Fadl (MedReviews, LLC, 2011)
A rare intratubular gonadal stromal tumor was present in the testis of a 45-year-old man who was admitted to our hospital with the chief complaint of gradual enlargement of the left testis. Tumoral markers were negative and no extension was observed. The tumor comprised an intratubular mixture of two types of tumor cells with intercellular junctions: the predominant tumor cells were consistent with a Sertoli cell origin and cells comprising the minor population consistent with a Leydig cell origin. The patient is disease free after 6-month follow-up. The case is considered to be a testicular mixed tubular Sertoli-Leydig cell tumor. It highlights a rare type of primary tumor of the testis that features a good prognosis.